(untitled) - Eiteman, David K. (Reading, MA, 2004)
The market-leading textbook in international finance, Multinational Business Finance is renowned for its authoritative coverage and clear explanations of contemporary international Finance. The thoroughly revised 10th edition features a new chapter on Political Risk, increased coverage of emerging markets, and an integrated focus on corporate governance issues. - In line with an ever-changing global environment, a new chapter on political risk that focuses on risk in three dimensions: firm-specific risk, country-specific risk, and global-specific risk. - Increased coverage of financial management issues in emerging markets throughout the text. - About twenty Mini-Cases, many of them new, focusing on such companies and organizations as Toyota Europe, Bang & Olufsen, Benecol, and Romanian Telecom. - Market-leading, lucid, accessible presentation of the complexities of international finance. Benefit: Professors view authors as authoritative sources in the field; students tend to keep the book as a reference tool. - Managerial emphasis in an international context. Benefit: Helps train tomorrow's business leaders, who will operate in an increasingly global financial environment.
Keywords: International business enterprises,Doanh nghiệp kinh doanh quốc tế; Finance,Tài chính